2009
DOI: 10.1073/pnas.0910950106
|View full text |Cite
|
Sign up to set email alerts
|

Iron fortification of rice seeds through activation of the nicotianamine synthase gene

Abstract: The most widespread dietary problem in the world is mineral deficiency. We used the nicotianamine synthase (NAS) gene to increase mineral contents in rice grains. Nicotianamine (NA) is a chelator of metals and a key component of metal homeostasis. We isolated activation-tagged mutant lines in which expression of a rice NAS gene, OsNAS3, was increased by introducing 35S enhancer elements. Shoots and roots of the OsNAS3 activationtagged plants (OsNAS3-D1) accumulated more Fe and Zn. Seeds from our OsNAS3-D1 plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
254
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 320 publications
(265 citation statements)
references
References 29 publications
8
254
3
1
Order By: Relevance
“…More importantly, the transgenic rice plants containing AtNAS and Pvferritin genes increased seed-Fe concentration by sixfold, with no yield penalty but such plants were earlier to flower, and that the Fe in the endosperm of the transgenic rice lines accumulated in spots, most probably as a consequence of spatially restricted ferritin accumulation (Wirth et al 2009). Biofortifying rice with NAS alone or in combination with ferritin has great potential in combating global human Fe deficiency in people dependent on rice for their sustenance (Lee et al 2009;Zheng et al 2010). Mugineic acid family phytosiderophores (MAs) play an important role in the uptake of Fe from the soil and Fe transport within the plant in graminaceous plants.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 99%
“…More importantly, the transgenic rice plants containing AtNAS and Pvferritin genes increased seed-Fe concentration by sixfold, with no yield penalty but such plants were earlier to flower, and that the Fe in the endosperm of the transgenic rice lines accumulated in spots, most probably as a consequence of spatially restricted ferritin accumulation (Wirth et al 2009). Biofortifying rice with NAS alone or in combination with ferritin has great potential in combating global human Fe deficiency in people dependent on rice for their sustenance (Lee et al 2009;Zheng et al 2010). Mugineic acid family phytosiderophores (MAs) play an important role in the uptake of Fe from the soil and Fe transport within the plant in graminaceous plants.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 99%
“…However, a similar approach using HvNAS1 in combination with soybean ferritin did not increase the seed Fe content (Masuda et al 2009). Activation tagging for OsNAS3 also resulted in increased Fe accumulation in roots, shoots, and seeds (Lee et al 2009b). OsNAS3-activated plants grown on a paddy field accumulated three times more Fe than WT plants and 9.6 times more NA in their seeds.…”
Section: Biofortification Of Rice With Fementioning
confidence: 99%
“…We have previously shown that grains from activation-tagged lines of OsNAS3 have 2.9-fold more Fe (Lee et al, 2009b). Furthermore, the hemoglobin levels in anemic mice fed with seeds from those transgenic plants recover to normal readings when animals are placed on that diet for two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-bioavailability using anemic mice was tested as previously described (Lee et al, 2009b). After three weeks of weaning for pathogen-free female Balb/c mice, one group was fed with AIN-93DIET (45 mg Fe kg -1 ) as a control diet (CD) and the second group was given an iron-depleted (ID) diet (modified AIN-93G diet containing 3 mg Fe kg -1 ).…”
Section: Mouse Feeding Experimentsmentioning
confidence: 99%
See 1 more Smart Citation